Metal-loaded titania nanoparticles and method for producing same
Metal-supported titania nanoparticles with silver and copper on their surface, treated with acyloxy groups and heated to 600°C, address the challenges of transparency, adhesion, and stability in photocatalyst coatings, achieving effective antimicrobial performance in both light and dark environments.
Patent Information
- Application Number
- JP2021058606
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Existing photocatalyst coatings for indoor building materials and daily necessities face challenges with transparency, adhesion, crack resistance, and the stability of antimicrobial metal components like silver and copper, especially when used without binders.
The development of metal-supported titania nanoparticles, where both silver and copper are supported on the surface, with acyloxy groups bonded to titanium atoms and heated to 600°C, creating a stable and binder-free photocatalyst coating with enhanced properties.
This solution provides a highly transparent, adhesive, and crack-resistant photocatalyst coating that maintains the stability of silver and copper, offering effective antibacterial and antiviral properties in both light and dark conditions without the need for binders.
Abstract
Description
[Technical field]
[0001] The present invention relates to metal-supported titania nanoparticles and a method for producing the same. [Background technology]
[0002] In recent years, in response to the improvement of hygiene consciousness, photocatalysts have been put to practical use in order to impart pathogen resistance to indoor building materials and daily necessities, and are often used in the form of coating a paint containing a photocatalyst on the surface. When light is irradiated onto the photocatalyst, for example, oxygen and moisture on the catalyst surface generate active oxygen species that lead to antimicrobial activity. Since the photocatalyst itself does not change before and after generating antimicrobial active species, it is used as a highly durable antimicrobial material. Generally, photocatalysts refer to catalysts that absorb ultraviolet light and exhibit photocatalytic activity, but in consideration of use in environments where ultraviolet light is difficult to reach, such as indoors, visible light catalysts that exhibit photocatalytic activity in response to light in the visible light range have been vigorously developed. The most commonly used visible light catalyst is a metal-containing titanium oxide powder or metal-containing titanium oxide sol, which is a titanium oxide powder or titanium oxide sol containing metals such as iron, platinum, gold, copper, and silver.
[0003] In indoor environments and situations where daily necessities are used, there are environments where there is no light, such as in the shade or at night, so metal-containing titanium oxide powders and metal-containing titanium oxide sols that contain anti-microbiotic metals such as silver and copper have been developed to exhibit anti-microbiotic properties even in dark places.
[0004] Meanwhile, photocatalytic coating films for indoor building materials, daily necessities, and the like are desired to be easily applied as a one-component system, to be highly transparent without impairing the design freedom of the substrate, and to have adhesion and crack resistance so as to prevent slipping or cracking when touched by hands, etc.
[0005] However, when a suspension of titanium oxide powder containing metal (trade names: Lumilesh (Showa Denko K.K.) or Cellmuse (Daicel Miraize K.K.)) dispersed in water is applied to a glass substrate or a highly transparent resin substrate, the white color derived from the titanium oxide powder is strongly observed, and the transparency of the glass substrate is impaired. In addition, when the coating film formed in this way is rubbed with a finger, the powder slides off.
[0006] As described above, when using metal-containing titanium oxide powder as a coating, there are problems with transparency and adhesion to substrates when used alone. To address this problem, a method is available in which a polymeric organic compound or a porous inorganic compound is used as a binder to fix the metal-containing titanium oxide powder in the binder and form a coating film.
[0007] However, polymer organic compound binders reduce the photocatalytic activity by coating the surface of metal-supported titanium oxide, and although porous inorganic compound binders have more voids than polymer organic compound binders and are less likely to reduce activity, they are hard and brittle and therefore lack crack resistance, which promotes the catalyst to slide off and shortens its service life, so the use of binders in photocatalysts poses the problem of compromising the inherent sustainability and antimicrobial activity of metal-supported titanium oxide.
[0008] For example, Patent Document 1 describes a virus inactivating agent containing a photocatalytic substance carrying a mixture containing a monovalent copper compound and a divalent copper compound on its surface. In the examples of Patent Document 1, Cu2O powder and a mixture of Cu2O powder and a silica-based binder are applied to a glass plate, and the mixture is allowed to come into contact with viruses under the same conditions for 30 minutes. 6 When the binder was used, the virus infectivity decreased by 10 5 The activity only decreased by about 10 times when the material carrier was used in combination with a binder.
[0009] Therefore, a method has been proposed in which an antimicrobial metal is supported on a titanium oxide sol that can be applied in a one-liquid system without using a binder, and a coating film of the antimicrobial metal-supported titanium oxide sol is formed by applying the one-liquid system. However, titanium oxide sol also has problems of clouding of the coating film and cracking, making it difficult to realize a coating film with high transparency and high durability. In fact, when a water-soluble titanium oxide sol with an extremely small X-ray particle diameter of 7 nm (product name CSB (Sakai Chemical Industry Co., Ltd.)) was applied on a glass substrate, the coating film became cloudy, and when titanium oxide synthesized by the method described in Non-Patent Document 1 was applied, cracks occurred. Thus, when using metal-containing titanium oxide powder and titanium oxide sol, it was difficult to form a binderless paint that is highly transparent and has high crack resistance and adhesion.
[0010] As mentioned above, metal-supported titanium oxide powder and sol for indoor coating have low adhesion to substrates and crack resistance when used alone, and these are reinforced by adding binders, etc., but the inherent antimicrobial activity and activity sustainability of metal-containing titanium oxide are impaired due to the binder coating the catalyst surface and the catalyst sliding off. In addition, while many indoor building materials and daily necessities require design in terms of color, metal-containing titanium oxide powder is a cloudy white powder, so the range of design is significantly limited. Therefore, there is a demand for a highly transparent visible light catalyst that is binderless, adheres to substrates, and has high physical resistance as a coating film.
[0011] Another problem with metal-containing titanium oxide powder and titanium oxide sol is the instability of the metal components contained separately from titanium oxide. For example, as described in Patent Document 2, when a silver complex is added to an aqueous solution in which titanium oxide is dispersed, the color of the solution gradually changes, and finally, silver precipitation is observed. This phenomenon in which precipitation occurs due to the instability of the metal components is often seen with elements with low ionization tendency such as silver and copper. Therefore, a method has been proposed in which silver and copper are combined and quaternary ammonium is contained in titanium oxide sol to stabilize the metal components with a stabilizer (Patent Document 2), and a method has been proposed in which the surface of silver is coated with a thiol-based ligand or titanium oxide (Non-Patent Document 2).
[0012] However, the method of Patent Document 2 involves safety concerns because it contains quaternary ammonium ions that are highly toxic to the human body. In addition, in the method of coating the surface of silver with a thiol ligand or titanium oxide, if the surface is completely coated, the elution of silver, which is an antimicrobial metal, is prevented, impairing the antimicrobial activity, while if the surface is partially coated, the antimicrobial metal silver is repeatedly eluted and reprecipitated, causing discoloration and precipitation.
[0013] As described above, there is a need for a visible light catalyst that allows antimicrobial metal components with low ionization tendency, such as silver and copper, to exist stably in a titanium oxide solution without causing precipitation, does not prevent the elution of these metals, and further, shows extremely high antibacterial activity even when applied in a very small amount and is highly transparent. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] JP 2013-166705 A [Patent Document 2] JP 2008-260684 A [Non-patent literature]
[0015] [Non-Patent Document 1] Journal of the Society of Inorganic Materials, Japan 11.313 (2004): 481-488. [Non-Patent Document 2] Journal of the Japan Color Materials Association, 2014, Vol. 87, No. 2, 43-49 Summary of the Invention [Problem to be solved by the invention]
[0016] The present invention aims to provide a highly transparent photocatalyst that can provide a one-component photocatalytic paint that is easy to apply without using a binder, has high adhesion to substrates and crack resistance, and allows the antimicrobial metal components silver and copper to exist stably in a titanium oxide solution without causing precipitation, and also has antibacterial and antiviral properties in the dark. [Means for solving the problem]
[0017] In view of the above object, the present inventors conducted intensive research and found that all of the above problems can be solved by a metal-loaded titania nanoparticle in which an acyloxy group is bonded to at least a part of titanium atoms present on the surface, and the mass loss at 200°C or higher when heated to 600°C using a differential thermal thermogravimetry analyzer is 5% by mass or more, and both silver and copper are loaded on the surface of the titania nanoparticle. Then, further research was conducted, and the present invention was completed. That is, the present invention includes the following configuration.
[0018] Item 1. A metal-loaded titania nanoparticle having a metal loaded on the surface of the titania nanoparticle, The titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, When the titania nanoparticles are heated to 600°C using a thermogravimetric and differential thermal analyzer, the mass loss at 200°C or higher is 5% by mass or more; and The metal-supported titania nanoparticles have both silver and copper supported on the surface of the titania nanoparticles.
[0019] Item 2. The metal nanoparticle-supporting titania nanoparticles according to Item 1, wherein the silver is in the form of silver nanoparticles and / or monovalent silver ions.
[0020] Item 3. The metal nanoparticle-supporting titania nanoparticles according to Item 1 or 2, wherein the silver is in the form of silver nanoparticles.
[0021] Item 4. The metal-supported titania nanoparticles according to any one of Items 1 to 3, wherein the copper is in the form of at least one selected from the group consisting of copper nanoparticles, monovalent copper ions, and divalent copper ions.
[0022] Item 5. The metal-supported titania nanoparticles according to any one of Items 1 to 4, wherein the copper is in the form of monovalent copper ions and / or divalent copper ions.
[0023] Item 6. The metal-supported titania nanoparticles according to any one of Items 1 to 5, wherein the copper is in the form of a divalent copper ion.
[0024] Item 7. The metal-supporting titania nanoparticles according to any one of Items 1 to 6, wherein the amount of the silver supported is 200 mass % or less based on the mass of titanium oxide in the titania nanoparticles.
[0025] Item 8. The metal-supporting titania nanoparticles according to any one of Items 1 to 7, wherein the amount of the copper supported is 200 mass % or less based on the mass of titanium oxide in the titania nanoparticles.
[0026] Item 9. The metal-supported titania nanoparticles according to any one of Items 1 to 8, wherein the acyloxy group is bonded to a titanium atom via a group represented by -OCOR (wherein R represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a hydroxyalkyl group having 1 to 2 carbon atoms).
[0027] Item 10. The metal-supported titania nanoparticles according to any one of Items 1 to 9, wherein the acyloxy group is an acyloxy group derived from at least one organic acid selected from the group consisting of monocarboxylic acids having 1 to 4 carbon atoms and hydroxycarboxylic acids having 2 to 3 carbon atoms.
[0028] Item 11. The metal-supported titania nanoparticles according to Item 10, wherein the organic acid is acetic acid and / or lactic acid.
[0029] Item 12. A photocatalyst comprising the metal-supported titania nanoparticles according to any one of items 1 to 11.
[0030] Item 13. A method for producing the metal-supported titania nanoparticles according to any one of items 1 to 11 or the photocatalyst according to item 12, (A) mixing a titanium-containing substance, an organic acid, and water to obtain a dispersion; (B) heating the dispersion obtained in step (A) at a temperature higher than 80° C. for at least 1 hour; (C1) A step of irradiating ultraviolet light to a dispersion obtained by mixing the dispersion obtained in the step (B), silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound; (C2) A step of mixing the dispersion liquid obtained in the step (B), silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound; or (C3) adding silver nanoparticles and / or a silver compound and copper nanoparticles and / or a copper compound to the dispersion liquid obtained in the step (B) and allowing the dispersion liquid to stand; A manufacturing method comprising:
[0031] Item 14. A dispersion of metal-supported titania nanoparticles, comprising 50 mass % or more of water and the metal-supported titania nanoparticles according to any one of items 1 to 11 or the photocatalyst according to item 12.
[0032] Item 15. The metal-supported titania nanoparticle dispersion according to Item 14, which does not contain any organic dispersant other than the organic acid.
[0033] Item 16. A coating material comprising the metal-supported titania nanoparticles according to any one of items 1 to 11 or the photocatalyst according to item 12.
[0034] Item 17. A coating film comprising the metal-supported titania nanoparticles according to any one of items 1 to 11 or the photocatalyst according to item 12.
[0035] Item 18. A coating product having the coating film according to item 17. Effect of the Invention
[0036] According to the present invention, it is possible to provide a photocatalytic paint that is easy to apply and is a one-component system without using a binder, and it is possible to obtain a highly transparent photocatalyst that has high adhesion to substrates and high crack resistance, and in which the antimicrobial metal components of silver and copper are present stably in a titanium oxide solution without causing precipitation, and that also has antibacterial and antiviral properties in dark places. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] In this specification, the term "containing" is a concept that encompasses all of "comprise," "consist essentially of," and "consist only of."
[0038] In this specification, when a numerical range is expressed as A to B, it means A or more and B or less.
[0039] In this specification, "titanium oxide" or "titania" refers not only to titanium dioxide (TiO2), but also includes titanium trioxide (Ti2O3), titanium monoxide (TiO), and titanium dioxide with oxygen deficiency, such as Ti4O7 and Ti5O9. Titanium oxide may also contain groups other than Ti-O-Ti, such as terminal OH groups, which are partially derived from the synthesis of titanium oxide. Titanium oxide may also have terminal OH groups to which organic acids or the like are bonded.
[0040] 1. Metal-loaded titania nanoparticles and photocatalysts The metal-loaded titania nanoparticles of the present invention are titania nanoparticles having a metal loaded on the surface thereof, wherein the titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface thereof, and when the titania nanoparticles are heated to 600°C using a thermogravimetry and differential thermal analyzer, the mass loss at 200°C or higher is 5% by mass or more, and both silver and copper are loaded on the surface of the titania nanoparticles.
[0041] By adopting such a configuration, the metal-supported titania nanoparticles of the present invention can adjust the average particle size and specific surface area of the titania nanoparticles, and when the form of the metal is metal nanoparticles (silver nanoparticles or copper nanoparticles), it is also possible to adjust the average particle size and specific surface area of the metal nanoparticles (silver nanoparticles or copper nanoparticles). In addition, the titania nanoparticles and metals (silver and copper) are firmly attached to each other, and are excellent in dispersibility and are difficult to aggregate, so that the metal components (silver and copper) are stably dispersed without the use of additives such as dispersants and stabilizers, and are excellent in discoloration resistance, coatability and transparency. In addition, the metal-supported titania nanoparticles and photocatalyst of the present invention have sufficient coatability and transparency without the use of separate dispersants and stabilizers, so that the visible light catalytic activity and dark place antibacterial and antiviral activity are not impaired by additives such as binders and dispersants, and the resistance to physical impacts such as rubbing is high, so that the visible light catalytic activity can be sustained. For this reason, the metal-supported titania nanoparticles of the present invention are useful as photocatalysts (especially visible light responsive photocatalysts) and photocatalyst coating materials. The metal-loaded titania nanoparticles of the present invention can have antimicrobial activity in bright places due to their photocatalytic activity, while in dark places they can have antimicrobial activity due to the action of the metals (silver and copper) present on the surface.
[0042] (1-1) Titania nanoparticles Usually, water, inorganic acids, free organic acids, etc. volatilize almost entirely at 200 ° C. or less. On the other hand, the titania nanoparticles constituting the metal-supported titania nanoparticles of the present invention have acyloxy groups bonded to at least some of the titanium atoms present on the surface, so they gradually desorb in the range of 200 to 600 ° C. For example, in the case of acetoxy groups, they gradually desorb in the range of 200 to 600 ° C., with a peak at about 260 ° C. Thus, the titania nanoparticles constituting the metal-supported titania nanoparticles of the present invention have acyloxy groups bonded to at least some of the titanium atoms present on the surface, so that the titania nanoparticles are prevented from coagulating during drying or firing, and cracks, peeling, etc. are unlikely to occur, and the coating properties and transparency are particularly excellent, and cracks, peeling, etc. can be suppressed, and furthermore, the metal described below is easily supported firmly, so that the visible light catalytic activity is also excellent. It is generally known in the art that the presence of acyloxy groups on the surface normally reduces visible light catalytic activity. However, in the present invention, as described above, the aggregation of titania nanoparticles during drying or calcination can be suppressed, and therefore the effect of suppressing cracks, peeling, etc. is particularly excellent. In addition, since the metal described below can be easily supported firmly, visible light catalytic activity can be improved despite the presence of acyloxy groups.
[0043] In addition, the titania nanoparticles preferably have a large amount of acyloxy groups bonded to titanium atoms present on the surface. When acyloxy groups are present on at least some of the titanium atoms present on the surface, they are gradually removed in the range of 200 to 600 ° C. as described above, so that when the temperature is raised by a thermogravimetry and differential thermal analyzer (TG-DTA), the mass loss at 200 ° C. or higher is large. That is, in the present invention, when the temperature is raised by a thermogravimetry and differential thermal analyzer (TG-DTA), the mass loss at 200 ° C. or higher means an index of the number of acetoxy groups bonded to titanium atoms present on the surface. For this reason, when the temperature is raised to 600 ° C. by a thermogravimetry and differential thermal analyzer (TG-DTA), the mass loss at 200 ° C. or higher is 5% by mass or more, preferably 7 to 20% by mass. In this case, the detailed conditions of the thermogravimetry and differential thermal analyzer (TG-DTA) are atmosphere: air, and heating rate: 3 ° C. / min.
[0044] As described above, the titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and the acyloxy groups are preferably bonded to the titanium atoms via a group represented by -OCOR (wherein R represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a hydroxyalkyl group having 1 to 2 carbon atoms). In other words, the acyloxy groups are preferably acyloxy groups derived from organic acids such as monocarboxylic acids having 1 to 4 carbon atoms and hydroxycarboxylic acids having 2 to 3 carbon atoms.
[0045] In the above R, examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, etc., and examples of the hydroxyalkyl group include a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, etc. In other words, examples of the monocarboxylic acid include formic acid, acetic acid, propionic acid, butyric acid, etc., and examples of the hydroxycarboxylic acid include glycolic acid, lactic acid, etc.
[0046] From the viewpoints of volatility, toxicity and decomposability, R is preferably a hydrogen atom, a methyl group, a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, etc., and from the viewpoints of water solubility and odor, a methyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, etc. are preferred. That is, from the viewpoints of volatility, toxicity and decomposability, the monocarboxylic acid is preferably formic acid, acetic acid, etc., and the hydroxycarboxylic acid is preferably glycolic acid, lactic acid, etc. Also, from the viewpoints of water solubility and odor, acetic acid, glycolic acid, lactic acid, etc. are particularly preferred. These organic acids can be used alone or in combination of two or more kinds.
[0047] The average particle size of the titania nanoparticles is preferably 1 to 5 nm, more preferably 2 to 4 nm. By setting the average particle size of the titania nanoparticles in this range, it is easy to support metals (silver and copper) moderately and more firmly, and it is easy to form a film with higher visible light catalytic activity and higher transparency. In addition, when the average particle size is small, the shrinkage during heating is large, so that cracks and peeling from the substrate tend to occur, but the metal-supported titania nanoparticles of the present invention are a material with excellent coatability even when titania nanoparticles with a small average particle size are used. In the present invention, the average particle size of the titania nanoparticles is measured by observation with an electron microscope (TEM).
[0048] The specific surface area of the above titania nanoparticles is 150 to 500 m 2 / g is preferable, and 200 to 400m 2 / g is more preferable. By setting the specific surface area of the titania nanoparticles in this range, it is easy to support metals (silver and copper) appropriately and more firmly, and it is easy to increase the visible light catalytic activity. The specific surface area of the titania nanoparticles is measured by the BET method.
[0049] In addition, the titania nanoparticles can have N, Cl and S element concentrations of 0 to 5000 ppm, particularly 0 to 1000 ppm. By setting the N, Cl and S element concentrations of the titania nanoparticles in this range, corrosion of the substrate is easily suppressed. This condition means that impurities derived from acidic titania precursors such as TiCl4 and TiOSO4 are absent or present in very small amounts. The N, Cl and S element concentrations of the titania nanoparticles are measured by WDX (fluorescent X-ray).
[0050] Furthermore, the crystalline form of the titania nanoparticles is preferably anatase type. By adopting anatase type, the visible light catalytic activity can be particularly improved. For the same reason, it is preferable that there is no crystalline form other than anatase type, and that the anatase type is 100%.
[0051] (1-2) Metal The metal species constituting the metal-supported titania nanoparticles of the present invention are both silver and copper. This makes it possible to particularly improve the antibacterial activity and antiviral activity in light and dark places (especially in dark places) compared to the case where each metal species is supported alone.
[0052] Among these, the form of silver is not particularly limited, but from the viewpoints of silver stability, antibacterial activity and antiviral activity in light and dark places (particularly dark places), etc., silver nanoparticles and / or monovalent silver ions are preferred, and silver nanoparticles are more preferred.
[0053] The form of copper is not particularly limited, but from the viewpoints of copper stability, antibacterial activity and antiviral activity in light and dark places (particularly dark places), etc., at least one selected from the group consisting of copper nanoparticles, monovalent copper ions and divalent copper ions is preferred, monovalent copper ions and / or divalent copper ions are more preferred, and divalent copper ions are even more preferred.
[0054] Usually, when metal ions or metal nanoparticles are added to titanium oxide, the metal ions are reduced over time to generate metal nanoparticles, regardless of the specific surface area of titanium oxide or the metal ion concentration, and the metal nanoparticles are thermally aggregated over time, which often results in metal precipitation. On the other hand, the titania nanoparticles constituting the metal-supported titania nanoparticles of the present invention have acyloxy groups bonded to at least some of the titanium atoms present on the surface, so that the metal ions and metal nanoparticles are stabilized on the titania nanoparticles, and reduction and thermal aggregation over time are suppressed.
[0055] When silver nanoparticles are used, the particle size growth of the silver nanoparticles is easily suppressed from the above viewpoint, and the average particle size of the silver nanoparticles is preferably 500 nm or less, more preferably 10 to 200 nm. By setting the average particle size of the supported silver nanoparticles within this range, it is easy to form a film with improved visible light catalytic activity and improved transparency. The average particle size of the silver nanoparticles is measured by observation with an electron microscope.
[0056] When copper nanoparticles are used, the particle size growth of the copper nanoparticles is easily suppressed from the above viewpoint, and the average particle size of the copper nanoparticles is preferably 500 nm or less, more preferably 1 to 100 nm. By setting the average particle size of the supported copper nanoparticles within this range, it is easy to form a film with improved visible light catalytic activity and improved transparency. The average particle size of the copper nanoparticles is measured by observation with an electron microscope.
[0057] In the present invention, the amount of silver supported on the surface of the titania nanoparticles is preferably 200% by mass or less, more preferably 0.0001 to 25% by mass, and even more preferably 0.01 to 10% by mass, based on the titanium oxide in the titania nanoparticles, from the viewpoints of antimicrobial activity (antibacterial activity and antiviral activity) and stability of the titania nanoparticles. By setting the amount within this range, it is easy to maintain the coatability and transparency, and it is easy to particularly improve the antibacterial activity, antiviral activity, and photocatalytic activity in a dark place.
[0058] In the present invention, the amount of copper supported on the surface of the titania nanoparticles is preferably 100% by mass or less, more preferably 0.0001 to 25% by mass, and even more preferably 0.01 to 10% by mass, based on the titanium oxide in the titania nanoparticles, from the viewpoints of antimicrobial activity (antibacterial activity and antiviral activity) and stability of the titania nanoparticles. By setting the amount within this range, it is easy to maintain the coatability and transparency, and it is easy to particularly improve the antibacterial activity, antiviral activity, and photocatalytic activity in a dark place.
[0059] In the present invention, the ratio of the amount of silver supported on the titania nanoparticles to the amount of copper supported (amount of silver supported / amount of copper supported) is not particularly limited, but from the viewpoints of antimicrobial activity (antibacterial activity and antiviral activity) and the stability of the titania nanoparticles, it is preferably 0.0001 to 2,000,000, more preferably 0.001 to 10,000, and even more preferably 0.01 to 100.
[0060] 2. Method for producing metal-loaded titania nanoparticles and photocatalyst Methods for supporting the above-mentioned metals on titania nanoparticles include a photoprecipitation method in which metal nanoparticles and / or metal complexes are mixed with titania nanoparticles and then irradiated with light to support the metals, and a method in which metal nanoparticles and / or metal complexes synthesized by any method are brought into contact with titania nanoparticles and mixed or allowed to stand to support the metals. Either method can be used in the present invention.
[0061] Specifically, the metal-supported titania nanoparticles and photocatalyst of the present invention are (A) mixing a titanium-containing substance, an organic acid, and water to obtain a dispersion; (B) heating the dispersion obtained in step (A) at a temperature higher than 80° C. for at least 1 hour; (C1) A step of irradiating ultraviolet light to a dispersion obtained by mixing the dispersion obtained in the step (B), silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound; (C2) A step of mixing the dispersion liquid obtained in the step (B), silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound; or (C3) adding silver nanoparticles and / or a silver compound and copper nanoparticles and / or a copper compound to the dispersion liquid obtained in the step (B) and allowing the dispersion liquid to stand; The method can be produced by a method comprising the steps of:
[0062] Among steps (C1), (C2), and (C3), the loading efficiency can be easily improved by applying energy from the outside, as in step (C1), while the adoption of step (C2) not only prevents the titania nanoparticle dispersion from becoming highly viscous, but also makes it easier to obtain uniform particles.
[0063] In any of the steps (C1), (C2) and (C3), the loading efficiency can be further improved by heating.
[0064] (2-1) Process (A) In step (A), a titanium-containing substance, an organic acid and water are mixed to obtain a dispersion.
[0065] The titanium-containing substance to be used is not particularly limited as long as it is a substance that becomes titanium oxide by heating. That is, the titanium-containing substance is preferably titanium oxide and / or a titanium oxide precursor, and specifically includes titanium oxide; titanium hydroxide; titanium alkoxide; titanium halide such as titanium trichloride and titanium tetrachloride (particularly neutralized with a base); metallic titanium, etc. These titanium-containing substances can be used alone or in combination of two or more. Among these, titanium alkoxide, titanium hydroxide, or titanium halide (particularly neutralized with a base) is preferred from the viewpoint of dispersibility, coatability, and visible light catalysis of the obtained titania, and titanium alkoxide is more preferred from the viewpoint of purity, dispersibility, coatability, transparency, and visible light catalysis.
[0066] Examples of titanium alkoxides include titanium tetraisopropoxide, titanium tetra n-butoxide, titanium tetra n-propoxide, and titanium tetraethoxide. From the viewpoints of cost, water solubility of by-products, coatability, and visible light catalytic properties, titanium tetraisopropoxide is preferred.
[0067] Depending on the combination of titanium alkoxide and organic acid, the resulting titania may act as a catalyst to liberate an ester compound that is poorly soluble in water, but this does not pose a problem for the titania itself (for example, in the combination of titanium tetra-n-butoxide and acetic acid, butyl acetate is produced and liberated at the mixing and heating stage). However, from the viewpoint of obtaining a uniform dispersion, it is preferable to adopt a combination of an organic acid and titanium alkoxide that can produce an organic acid alkoxide with excellent water solubility.
[0068] Titanium halides (titanium tetrachloride, titanium trichloride, etc.) are preferably neutralized with a base and the precipitate washed before use from the viewpoints of impurities (halogens), corrosion of the reactor during mass production, crystallinity control, coatability, transparency, and visible light catalysis. In that case, from the viewpoint of dispersibility of the obtained titania, it is preferable to use without drying.
[0069] When using a solid such as titanium oxide or metallic titanium as the titanium-containing substance, the average particle size is preferably 100 nm or less, more preferably 50 nm or less. There is no particular lower limit, but it is usually about 1 nm. If the particle size is large, it can be ground in a dry or wet manner using a planetary ball mill, paint shaker, or the like. The average particle size of solids such as titanium oxide or metallic titanium is measured by observation with a transmission electron microscope (TEM).
[0070] The concentration of the titanium-containing substance in the dispersion produced in step (A) is preferably 0.01 to 5 mol / L, more preferably 0.05 to 3 mol / L, from the viewpoints of productivity, viscosity of the reaction liquid, coatability, transparency, and visible light catalytic properties.
[0071] The acid used in the reaction is an organic acid, and a volatile acid is preferable. n H 2n+1 Examples of the monocarboxylic acid include monocarboxylic acids having 1 to 4 carbon atoms represented by COOH (n=0 to 3), and hydroxycarboxylic acids having 2 to 3 carbon atoms.
[0072] From the viewpoints of volatility, harmfulness, and decomposability, the monocarboxylic acid is preferably formic acid where n = 0 and acetic acid where n = 1, and the hydroxycarboxylic acid is preferably glycolic acid, lactic acid, etc., and from the viewpoints of water solubility and odor, acetic acid, glycolic acid, lactic acid, etc. are particularly preferred. These organic acids can be used alone or in combination of two or more kinds.
[0073] From the viewpoints of dispersibility, coatability, transparency, visible light catalysis and cost, the amount of organic acid used is preferably adjusted so that the number of moles of acyloxy groups is 1.5 moles or more, particularly 2 moles or more, per mole of titanium in the titanium-containing substance. The more organic acid is used, the easier it is to improve stability over time, coatability, transparency, etc. The upper limit is not particularly limited, but it is preferable to adjust the number of moles of acyloxy groups to be usually 10 moles or less per mole of titanium in the titanium-containing substance.
[0074] The concentration of the organic acid in the dispersion obtained in step (A) is preferably from 0.02 to 10 mol / L, more preferably from 0.1 to 7 mol / L, from the viewpoints of dispersibility, coatability, transparency, visible light catalytic properties, and cost.
[0075] As the reaction solvent, it is preferable to use an aqueous solvent such as water as the main component (specifically, for example, 50% by mass or more), but it may contain an alcohol or an ester during the reaction.
[0076] For example, when titanium tetraisopropoxide is used as a raw material, isopropyl alcohol is generated by reaction with an organic acid. Also, isopropyl esters of organic acids may be generated by heating. That is, alcohol or ester may be added to the dispersion obtained by step (A), or may be generated in the system. The alcohol or ester may be removed by heating in an open system at 100°C or less, or may be removed by reducing pressure, or may remain in the reaction liquid.
[0077] In addition, when alcohol is contained in the dispersion liquid, the average particle size of the obtained titania nanoparticles and the metal-supported titania nanoparticles of the present invention tends to be small, and therefore alcohol may be intentionally added in order to control the average particle size.
[0078] In the present invention, inorganic acids (especially strong inorganic acids) such as nitric acid, hydrochloric acid, and sulfuric acid, which are usually used in the hydrothermal synthesis reaction of titania nanoparticles, are preferably not used in principle, not only because the crystal form of the obtained titania nanoparticles is a mixture of anatase type and brookite type, but also from the viewpoint of storage stability of the obtained dispersion, corrosion of the equipment, impurities, drainage, etc. However, when the dispersibility, transparency, uniformity, etc. of the raw material are improved to facilitate handling, it can be used supplementarily within a range that does not impair the effect, for example, within a range of 0.01 mol / L or less. In this case, the concentrations of N, Cl, and S elements in the dispersion obtained in step (A) are all 0.01 mol / L or less.
[0079] The pH of the dispersion obtained in step (A) is preferably 2 or more and less than 6, more preferably 2.1 to 5, from the viewpoints of equipment corrosion, handling safety, dispersibility, and the like.
[0080] In step (A), the method of preparing the dispersion is not particularly limited, and the titanium-containing substance, organic acid, and water (solvent) may be mixed simultaneously or successively. In particular, in mass production scale, it is preferable to mix the organic acid and water (solvent) and then add the titanium-containing substance while stirring, from the viewpoint of being less likely to aggregate and form large lumps and making it easier to continue stirring. On the other hand, in laboratory scale, it is preferable to mix the titanium-containing substance and organic acid and then add water while stirring.
[0081] (2-2) Process (B) In step (B), the dispersion obtained in step (A) is heated at a temperature higher than 80° C. for 1 hour or more.
[0082] Step (B) may be carried out under normal pressure or under pressure in a closed vessel. From the viewpoint of reducing the average particle size of the titania nanoparticles and the metal nanoparticle-supported titania nanoparticles of the present invention, it is preferable to carry out the reaction under normal pressure, specifically 0.09 to 0.11 MPa. When carrying out the reaction under pressure, it is preferable to carry out the reaction for a short time (for example, about 5 to 30 minutes) at 0.2 MPa or less (0.11 to 0.2 MPa) from the viewpoint of easily forming a film having high visible light catalytic activity and high transparency.
[0083] During heating, stirring is preferred from the viewpoint of sufficiently reacting the titanium-containing substance with the organic acid and water. The stirring method is not particularly limited and can be performed according to a conventional method. The stirring time is preferably 1 hour or more, more preferably 1.5 hours or more, from the viewpoint of sufficiently reacting the titanium-containing substance with the organic acid and water. The upper limit of the stirring time is not particularly limited, but is usually 240 hours.
[0084] The heating temperature is higher than 80° C., preferably 82° C. or higher. If the heating temperature is lower than 80° C., cracks are likely to occur, the coating properties are poor, and the coating falls off easily, making it difficult to form a coating film. There is no particular upper limit to the heating temperature, but when the reaction is carried out at normal pressure, it is usually 120° C.
[0085] The pH of the dispersion obtained in such step (B) is preferably 2 or more and less than 6, more preferably 2.1 to 5, from the viewpoints of equipment corrosion, handling safety, dispersibility, and the like.
[0086] (2-3) Process (C1) In step (C1), the dispersion obtained by mixing the dispersion obtained in step (B), silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound is irradiated with ultraviolet light.
[0087] When silver nanoparticles are used as silver, known or commercially available products can be used. When silver nanoparticles are synthesized, they can be synthesized based on the method described in, for example, Silver Nanoparticles, Journal of the Adhesion Society of Japan, 2008, Vol. 44, No. 11, pp. 414-419.
[0088] The average particle size of the silver nanoparticles that can be used in this case is not particularly limited, and from the viewpoints of antibacterial and antiviral activity and dispersion stability of the nanoparticles, it is preferably 0.1 to 500 nm, more preferably 1 to 100 nm.
[0089] When using a silver salt as the silver compound, since the dispersion (sol) containing titania nanoparticles obtained in steps (A) and (B) is acidic, it is preferable to avoid the dispersion after step (C1) becoming basic. For this reason, the silver salt is preferably a silver salt whose aqueous solution is acidic or neutral. Specific examples of such silver salts include silver chloride (I), silver nitrate (I), organic acid silver (silver lactate (I), silver acetate (I), silver citrate (I), silver myristate (I), etc.), silver sulfide (I), silver oxide (I), silver phosphate (I), silver carbonate (I), silver bromide (I), silver iodide (I), etc. These silver salts can also be used as silver nanoparticle precursors that become silver nanoparticles by reduction.
[0090] The above silver nanoparticles and silver compounds can be used alone or in combination of two or more kinds.
[0091] When copper nanoparticles are used as copper, known or commercially available products can be used. When synthesizing copper nanoparticles, for example, they can be synthesized based on the method described in Cu and Cu-Based Nanoparticles: Synthesis and Applications in Catalysis Chemical Reviews, 2016, 116 (6), 3722-3811.
[0092] The average particle size of the copper nanoparticles that can be used in this case is not particularly limited, and from the viewpoints of antibacterial and antiviral activity and dispersion stability of the nanoparticles, it is preferably 0.1 to 200 nm, more preferably 1 to 50 nm.
[0093] When using a copper salt as the copper compound, since the dispersion (sol) containing titania nanoparticles obtained in steps (A) and (B) is acidic, it is preferable to avoid the dispersion after step (C1) becoming basic. For this reason, the copper salt is preferably a copper salt whose aqueous solution is acidic or neutral. Specific examples of such copper salts include organic acid copper (copper(II) acetate, copper(II) lactate, copper(II) citrate, copper(II) myristate, etc.), copper(II) sulfate, copper(II) nitrate, copper(II) phosphate, copper(I) oxide, copper(II) oxide, copper(II) carbonate, etc. These copper salts can also be used as silver nanoparticle precursors that become silver nanoparticles by reduction.
[0094] The above copper nanoparticles and copper compounds can be used alone or in combination of two or more kinds.
[0095] Among these, although not particularly limited, from the viewpoints of the stability of copper in the obtained metal-supported titania nanoparticles, the antibacterial activity and antiviral activity in light and dark places (particularly dark places), etc., copper nanoparticles, copper nanoparticle precursors, monovalent copper salts, divalent copper salts, etc. are preferred, monovalent copper salts, divalent copper salts, etc. are more preferred, and divalent copper salts are even more preferred.
[0096] In step (C1), the amount of silver nanoparticles and / or silver compound used is preferably 200 mass% or less, more preferably 0.0001 to 25 mass%, and even more preferably 0.01 to 10 mass%, in terms of the mass of silver element in the silver nanoparticles and / or silver compound, relative to the solid content when the dispersion obtained in step (B) is heated at 200° C., from the viewpoints of dispersibility, transparency, antimicrobial activity (antibacterial activity and antiviral activity), stability of titania nanoparticles, etc. By setting it in this range, the coatability and transparency are easily maintained, and antibacterial activity, antiviral activity, and photocatalytic activity in a dark place are particularly easily improved.
[0097] In step (C1), the amount of copper nanoparticles and / or copper compound used is preferably 100% by mass or less, more preferably 0.0001 to 25% by mass, and even more preferably 0.01 to 10% by mass, based on the solid content when the dispersion obtained in step (B) is heated at 200 ° C., in terms of dispersibility, transparency, antimicrobial activity (antibacterial activity and antiviral activity), stability of titania nanoparticles, etc., in terms of the mass of copper element in the copper nanoparticles and / or copper compound. By setting it in this range, it is easy to maintain the coatability and transparency, and it is easy to particularly improve the antibacterial activity, antiviral activity, and photocatalytic activity in the dark.
[0098] In step (C1), the ratio of the amount of silver nanoparticles and / or silver compounds used to the amount of copper nanoparticles and / or copper compounds used (amount of silver nanoparticles or silver compounds used / amount of copper nanoparticles or copper compounds used) is not particularly limited, but is preferably 0.0001 to 2,000,000, more preferably 0.001 to 10,000, and even more preferably 0.01 to 100, from the viewpoints of antimicrobial activity (antibacterial activity and antiviral activity) and the stability of titania nanoparticles.
[0099] In step (C1), the irradiation intensity of the ultraviolet light is set to 10 μW / cm from the viewpoints of ease of supporting silver and copper on the titania nanoparticles, visible light catalytic activity, reaction rate, productivity, etc. 2 More than 100 μW / cm is preferable. 2 More preferably, 1 mW / cm 2 The upper limit of the irradiation intensity of the ultraviolet light is not particularly limited, but is usually 2 W / cm. 2 It is.
[0100] In step (C1), the ultraviolet light irradiation time is 5 minutes or more, which is favorable for the generation of silver and copper on the surface of the titania nanoparticles, but from the viewpoint of visible light catalytic activity, etc., irradiation for 10 minutes or more is preferable, and irradiation for 20 minutes or more is more preferable. The upper limit of the ultraviolet light irradiation time is not particularly limited, but is usually 5 hours.
[0101] In step (C1), the ultraviolet light may be irradiated in pulses repeatedly at a predetermined time interval, or may be irradiated continuously without interruption, and can be appropriately set depending on the required properties.
[0102] In step (C1), the ultraviolet light irradiation is preferably performed at room temperature (20° C.) or higher, more preferably at 50° C. or higher, from the viewpoints of ease of supporting silver and copper on titania nanoparticles, visible light catalytic activity, reaction rate, productivity, etc. The upper limit of the temperature is not particularly limited, but is usually 100° C. when the reaction is performed at normal pressure.
[0103] In step (C1), during the ultraviolet light irradiation, it is preferable to stir the dispersion obtained in step (B) from the viewpoint of sufficiently reacting the silver nanoparticles and / or silver compound with the copper nanoparticles and / or copper compound. The stirring method is not particularly limited and can be performed according to a conventional method.
[0104] Step (C1) may be carried out under an air atmosphere or an anaerobic atmosphere. Specific examples of the anaerobic atmosphere include an inert gas atmosphere such as a nitrogen atmosphere or an argon atmosphere.
[0105] The pH of the dispersion thus obtained differs depending on the type of metal added and the amount of the metal added, but is preferably 1 to 3.
[0106] Thereafter, the metal-supported titania nanoparticles of the present invention can be recovered by precipitating and centrifuging the metal-supported titania nanoparticles in a conventional manner, etc. In other words, titania nanoparticles having a large amount of acyloxy groups bonded to titanium atoms present on the surface and silver and copper supported on the surface can be obtained.
[0107] (2-4) Steps (C2) and (C3) In the present invention, instead of the above-mentioned step (C1), step (C2) may be adopted in which the dispersion obtained in step (B) is mixed with silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound, or step (C3) may be adopted in which silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound are added to the dispersion obtained in step (B) and allowed to stand.
[0108] The silver nanoparticles, silver compound, copper nanoparticles and copper compound used are the same as those in the above-mentioned step (C1). The amounts of the silver nanoparticles, silver compound, copper nanoparticles and copper compound used are also the same as those in the above-mentioned step (C1).
[0109] In step (C2), the method of mixing the dispersion obtained in step (B), the silver nanoparticles and / or silver compound, and the copper nanoparticles and / or copper compound is not particularly limited and can be performed according to a conventional method. For example, the silver nanoparticles and / or silver compound, and the copper nanoparticles and / or copper compound can be added to the dispersion obtained in step (B) and stirred. The stirring method is not particularly limited and can be performed according to a conventional method.
[0110] In step (C2), the dispersion obtained in step (B), the silver nanoparticles and / or silver compound, and the copper nanoparticles and / or copper compound are mixed at room temperature (20° C.) or higher, and more preferably at 50° C. or higher, from the viewpoints of ease of supporting silver and copper on titania nanoparticles, visible light catalytic activity, reaction rate, productivity, etc. The upper limit of the temperature is not particularly limited, but is usually 100° C. when reacting at normal pressure.
[0111] Steps (C2) and (C3) may be carried out under an air atmosphere or under anaerobic conditions, specifically under an inert gas atmosphere such as a nitrogen atmosphere or an argon atmosphere.
[0112] The pH of the dispersion thus obtained differs depending on the type of metal added and the amount of the metal added, but is preferably 1 to 3.
[0113] Thereafter, the metal-supported titania nanoparticles of the present invention can be recovered by precipitating and centrifuging the metal-supported titania nanoparticles in a conventional manner, etc. In other words, titania nanoparticles in which a large amount of acyloxy groups are bonded to titanium atoms present on the surface, silver and copper are supported on the surface, and are firmly adhered to the surface can be obtained.
[0114] 3. Metal nanoparticle-supported titania nanoparticle dispersion The metal-supported titania nanoparticle dispersion of the present invention (particularly the photocatalyst dispersion, and further the visible light responsive photocatalyst dispersion) can be prepared by adding a dispersion step such as ultrasonic dispersion as necessary, using a reaction liquid that has undergone the above steps (A), (B), (C1), (C2) or (C3). At this time, in the conventional visible light responsive photocatalyst dispersion, a uniform dispersion could not be obtained unless a dispersant was used, so in the present invention, a dispersant may be added, but even without adding a dispersant, a dispersion with much better dispersibility than that of a normal visible light responsive photocatalyst can be obtained. As a result of the good dispersibility, the coating has excellent crack resistance. In addition, as a result of not needing to add a dispersant, a dense titania coating is also possible, and in addition to being excellent in coatability and transparency, the visible light catalytic activity is also excellent.
[0115] In this case, in the metal-supported titania nanoparticle dispersion of the present invention, the content of water, which is the main solvent, is preferably 50 mass% or more, particularly 60 mass% or more, with the total amount of the metal-supported titania nanoparticle dispersion of the present invention being 100 mass%, from the viewpoints of ease of coating, film properties of the coating, etc.
[0116] It is also possible to take out the metal-supported titania nanoparticles of the present invention from the reaction solution and change the solvent. The water may be removed from the reaction solution by centrifugation or a filtration membrane, and replaced with an organic solvent. In this case, it is preferable not to dry the metal-supported titania nanoparticles of the present invention from the viewpoints of dispersibility, transparency, etc.
[0117] Examples of the organic solvent used in the dispersion include alcohols, etc. Examples of the alcohols include aliphatic alcohols having 1 to 6 carbon atoms, such as methanol, ethanol, and isopropanol, as well as non-aliphatic alcohols, such as α-terpineol, glycol solvents, such as butyl carbitol (diethylene glycol monobutyl ether), hexylene glycol (2-methyl-2,4-pentanediol), ethylene glycol-2-ethylhexyl ether, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether, and diols, such as 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.
[0118] In addition, even if it does not have an OH group, it is sufficient if it has affinity with titania and other solvents (water, alcohol, etc.), and examples thereof include diethylene glycol butyl methyl ether, tripropylene glycol dimethyl ether, triethylene glycol dimethyl ether, diethylene glycol dibutyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol diacetate, triethylene glycol diacetate, tetraethylene glycol diacetate, etc. Among them, from the viewpoint of boiling point, etc., diethylene glycol monobutyl ether acetate, tetraethylene glycol dimethyl ether, etc. are preferable.
[0119] The metal-supported titania nanoparticle dispersion of the present invention can be made into a paint by adjusting the viscosity according to the application. For example, when it is used for spin coating, dip coating, spraying, etc., it is adjusted to a low viscosity, when it is used for brush coating, squeegee method, etc., it is adjusted to a higher viscosity, and when it is used for screen printing, it is preferable to adjust the viscosity even higher to suppress the flowability. The coating film of the present invention obtained in this way is a dense coating as described above.
[0120] The coated product of the present invention having the coating film of the present invention thus obtained is not particularly limited, and examples thereof include building materials, building exteriors, building interiors, window frames, window glass, various lenses, structural members, building equipment such as housing, cooking utensils, textile products, furniture, displays, display protective films, plumbing members, vehicle lamp covers and window glass, exteriors of mechanical equipment or articles, dustproof covers and paints, display devices, their covers, traffic signs, various display devices, displays such as billboards, sound insulation walls for roads and railways, exteriors and paints of bridges and guardrails, interiors and paints of tunnels, insulators, solar cell covers, solar hot water heater heat collector covers, and other exterior parts of electronic and electrical equipment used outside, particularly transparent members, exteriors of vinyl greenhouses, greenhouses, and the like. EXAMPLES
[0121] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.
[0122] [Example 1] 120g (2mol) of acetic acid was added to 142.1g (0.5mol) of titanium tetraisopropoxide and stirred for 60 minutes, and 538g of water was added. This dispersion had a titanium tetraisopropoxide concentration of 0.625mol / L, an acetic acid concentration of 2.5mol / L, and a pH of 2.2. A large amount of translucent precipitate was generated, but when the mixture was stirred for 60 minutes and then heated to 70℃, all of the precipitate dissolved. In this dispersion, the concentration of inorganic acid, N, Cl, and S elements were all 0mol / L.
[0123] After that, the mixture was stirred at normal pressure (0.10 MPa) and 85°C for 3 hours, and a semi-transparent uniform titania dispersion was obtained without using an organic dispersant. When ultrasonic dispersion was added to this dispersion, the viscosity was reduced and the transparency increased. The water content of this dispersion was 67% by mass and the pH was 2.3.
[0124] The dispersion was dried to obtain titania nanoparticles. The BET specific surface area of the titania nanoparticles was measured and found to be 250 m 2 / g. TEM observation revealed that the average particle size was approximately 3 nm. X-ray diffraction analysis of the crystallinity of the obtained titania nanoparticles revealed that they were 100% anatase type (no other crystal forms were present).
[0125] The dispersion was kept at 200°C using a moisture meter and dried until there was no mass loss. The TG-DTA of the titania nanoparticles was measured by heating the dispersion to 600°C at a temperature increase rate of 3°C / min in an air atmosphere. The mass loss above 200°C was 10% by mass. This mass loss above 200°C corresponds to the mass loss due to the elimination of acetic acid, an organic acid. Since most of the liberated acetic acid volatilizes below 200°C, the fact that the mass loss above 200°C is 10% by mass suggests that a large amount of acetyl groups, which are acyloxy groups, are bonded to titanium atoms in the form of -OCOCH3 on the surface of the titania nanoparticles.
[0126] In an air atmosphere, 614 mg of silver nitrate (I) and 3 mg of copper nitrate (II) trihydrate were added to 15 g (5.2 mass%) of this dispersion so that the silver and copper were 50 mass% and 0.1 mass% on a metal weight basis relative to the titania nanoparticles (titanium oxide) contained in the dispersion, respectively, and the mixture was stirred thoroughly, and then allowed to stand at room temperature for one week to obtain a dispersion. Even after leaving the mixture for another week, there was no change in the color of the solution, and it was confirmed that the silver and copper components were stably present in the solution. At this time, the pH of the solution was 1.7. In addition, the form of the silver supported on the titania nanoparticles was silver nanoparticles (average particle size 50 nm), and the form of the copper was divalent copper ions.
[0127] Next, this dispersion was applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the substrate was dried at 80°C. The transmittance of 400 to 800 nm (visible light region) was measured using an ultraviolet-visible spectrometer (UV3400 manufactured by Shimadzu Corporation), and the average transmittance of the coating film was 97%. In addition, no cracks were observed in the coating film formed on the glass substrate. From this, it can be understood that Example 1 has excellent crack resistance. In addition, even when the obtained glass substrate sample surface was strongly rubbed with a finger, no slipping was observed. From this, it can be understood that Example 1 has a high degree of adhesion between the titania nanoparticles and the glass surface. When an antibacterial test against Escherichia coli (K-12) was performed using a method based on JISZ2801 (dark place, 35°C, 1 hour), a very high antibacterial activity value of 3.0 or more (lower limit of detection) was obtained.
[0128] [Example 2] In an air atmosphere, 1 mg of silver nitrate (I) and 741 mg of copper nitrate (II) trihydrate were added to 15 g (5.2 mass%) of a dispersion containing titania nanoparticles obtained by the same method as in Example 1 so that the silver was 0.1 mass% and the copper was 25 mass% based on the metal weight of the titania nanoparticles (titanium oxide) contained in the dispersion, and the mixture was stirred well, and then left to stand at room temperature for one week to obtain a dispersion. Even after leaving it for another week, the color of the solution did not change, and it was confirmed that the silver and copper components were stably present in the solution. At this time, the pH of the solution was 1.6. In addition, the form of the silver supported on the titania nanoparticles was silver nanoparticles (average particle size 50 nm), and the form of the copper was divalent copper ions.
[0129] Next, this dispersion was applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the substrate was dried at 80°C. The transmittance of 400 to 800 nm (visible light region) was measured using an ultraviolet-visible spectrometer (UV3400 manufactured by Shimadzu Corporation), and the average transmittance of the coating film was 95%. In addition, no cracks were observed in the coating film formed on the glass substrate. From this, it can be understood that Example 2 has excellent crack resistance. In addition, even when the obtained glass substrate sample surface was strongly rubbed with a finger, no slipping was observed. From this, it can be understood that Example 2 has a high degree of adhesion between the titania nanoparticles and the glass surface. Furthermore, when an antibacterial test against Escherichia coli (K-12) was performed using a method based on JISZ2801 (dark place, 35°C, 1 hour), a very high antibacterial activity value of 3.0 or more (lower limit of detection) was obtained.
[0130] [Example 3] In an air atmosphere, 307 mg of silver nitrate (I) and 371 mg of copper nitrate (II) trihydrate were added to 15 g (5.2 mass%) of a dispersion containing titania nanoparticles obtained by the same method as in Example 1 so that the silver was 25 mass% and the copper was 12.5 mass% based on the metal weight of the titania nanoparticles (titanium oxide) contained in the dispersion, and the mixture was stirred well, and then left to stand at room temperature for one week to obtain a dispersion. Even after leaving the mixture for another week, the color of the solution did not change, and it was confirmed that the silver and copper components were stably present in the solution. At this time, the pH of the solution was 1.6. In addition, the form of the silver supported on the titania nanoparticles was silver nanoparticles (average particle size 50 nm), and the form of the copper was divalent copper ions.
[0131] Next, this dispersion was applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the substrate was dried at 80°C. The transmittance of 400 to 800 nm (visible light region) was measured using an ultraviolet-visible spectrometer (UV3400 manufactured by Shimadzu Corporation), and the average transmittance of the coating film was 99%. In addition, no cracks were observed in the coating film formed on the glass substrate. From this, it can be understood that Example 3 has excellent crack resistance. In addition, even when the obtained glass substrate sample surface was strongly rubbed with a finger, no slipping was observed. From this, it can be understood that Example 3 has a high degree of adhesion between the titania nanoparticles and the glass surface. Furthermore, when an antibacterial test against Escherichia coli (K-12) was performed using a method based on JISZ2801 (dark place, 35°C, 1 hour), a very high antibacterial activity value of 3.0 or more (lower limit of detection) was obtained.
[0132] [Example 4] In an air atmosphere, 60 mg of silver nitrate (I) and 148 mg of copper nitrate (II) trihydrate were added to 15 g (5.2 mass%) of a dispersion containing titania nanoparticles obtained by the same method as in Example 1 so that the silver was 5 mass% and the copper was 10 mass% based on the metal weight of the titania nanoparticles (titanium oxide) contained in the dispersion, and the mixture was stirred well, and then left to stand at room temperature for one week to obtain a dispersion. Even after leaving it for another week, the color of the solution did not change, and it was confirmed that the silver and copper components were stably present in the solution. At this time, the pH of the solution was 2.4. In addition, the form of the silver supported on the titania nanoparticles was silver nanoparticles (average particle size 50 nm), and the form of the copper was divalent copper ions.
[0133] Next, this dispersion was applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the substrate was dried at 80°C. The transmittance of 400 to 800 nm (visible light region) was measured using an ultraviolet-visible spectrometer (UV3400 manufactured by Shimadzu Corporation), and the average transmittance of the coating film was 99%. In addition, no cracks were observed in the coating film formed on the glass substrate. From this, it can be understood that Example 4 has excellent crack resistance. In addition, even when the obtained glass substrate sample surface was strongly rubbed with a finger, no slipping was observed. From this, it can be understood that Example 4 has a high degree of adhesion between the titania nanoparticles and the glass surface. Furthermore, when an antibacterial test against Escherichia coli (K-12) was performed using a method based on JISZ2801 (dark place, 35°C, 1 hour), a very high antibacterial activity value of 3.0 or more (lower limit of detection) was obtained.
[0134] In addition, this dispersion was applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the surface of the sample was dried at 80°C. A wipe test was then carried out 400 times with moistened cotton under a load of 750g. An antibacterial test against E. coli (K-12) was then carried out using a method based on JIS Z2801 (in the dark, at 35°C, for 1 hour). The antibacterial activity value was 3.0 or more (lower limit of detection), which was a very high value, the same as before the wipe test. This confirmed that the coating film had high durability.
[0135] This dispersion was then applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the substrate was dried at 80° C. A liquid containing feline coronavirus was dropped onto the obtained glass sample, and the antiviral activity value was tested by a method based on JIS R1756 after the sample was exposed to the liquid for 8 hours at 1000 lux and in a dark place, which gave a value of 4.4 (lower limit of detection) at 1000 lux and 3.7 in a dark place.
[0136] [Comparative Example 1] In an air atmosphere, 60 mg of silver nitrate (I) was added to 15 g (5.2 mass%) of a dispersion containing titania nanoparticles obtained by the same method as in Example 1 so that silver was 5 mass% based on the metal weight relative to the titania nanoparticles (titanium oxide) contained in the dispersion, and the mixture was stirred well, and then left to stand at room temperature for one week to obtain a dispersion. Even after leaving it for another week, there was no change in the color of the solution, and it was confirmed that the silver component was stably present in the solution. At this time, the pH of the solution was 2.5. In addition, the form of silver supported on the titania nanoparticles was silver nanoparticles (average particle size 50 nm).
[0137] Next, this dispersion was applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the substrate was dried at 80°C. The transmittance of 400-800 nm (visible light region) was measured using an ultraviolet-visible spectrometer (UV3400 manufactured by Shimadzu Corporation), and the average transmittance of the coating film was 99%. In addition, even when the obtained glass substrate sample surface was strongly rubbed with a finger, no slipping was observed. From this, it can be understood that the adhesion between the titania nanoparticles and the glass surface in Comparative Example 1 is high. Furthermore, when an antibacterial test against Escherichia coli (K-12) was performed using a method based on JISZ2801 (dark place, 35°C, 1 hour), a very high antibacterial activity value of 4.0 or more was obtained.
[0138] This dispersion was then applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the substrate was dried at 80° C. A liquid containing feline coronavirus was dropped onto the obtained glass sample, and the antiviral activity value was tested by a method based on JIS R1756 after the sample was left in contact with the liquid for 8 hours at 2000 lux and in a dark place, which gave a value of 4.5 (lower limit of detection) at 2000 lux and 0.3 in a dark place.
[0139] [Comparative Example 2] Titania nanoparticles ST-01 (Ishihara Sangyo Kaisha, Ltd., specific surface area 300 m 2 / g, average particle size calculated from specific surface area 5 nm, no acyl group on the surface) 10 g, acetic acid 30 g, water 160 g were added, silver nitrate (I) 0.31 g, copper nitrate (II) trihydrate 0.74 g were added so that silver was 25 mass% and copper was 25 mass% on a metal weight basis with respect to titania nanoparticles (titanium oxide) contained in the dispersion, and after stirring well, it was left at room temperature, but black precipitation was observed within a few days, and a uniform solution was not obtained. From this, it was confirmed that silver and copper were not stably present in Comparative Example 2 as in Example 1. Since antimicrobial metal was not stably present, further tests were abandoned.
[0140] [Comparative Example 3] 190 g of water was added to 10 g of Lumilesh CT-2 (a commercially available titanium oxide-based visible light responsive catalyst, no acyl groups present on the surface) and ultrasonic dispersion was performed, but a homogeneous solution was not obtained.
[0141] In addition, when this suspension was applied onto a glass substrate, the titania film was completely opaque. From this, it can be understood that the dispersibility of Comparative Example 3 is inferior to that of Example 1. In addition, the adhesion between the titania nanoparticles and the glass surface was low, and the titania nanoparticles slid off when lightly rubbed with a finger.
[0142] Next, this suspension was applied (spin-coated) to a glass substrate with a thickness of 0.7 mm, and the substrate was dried at 80°C. The transmittance of 400 to 800 nm (visible light region) was measured using an ultraviolet-visible spectrometer (UV3400 manufactured by Shimadzu Corporation), and the average transmittance of the coating film was 58%. In addition, when the obtained glass substrate sample surface was lightly rubbed with a finger, the titania nanoparticles slid off. From this, it can be understood that the adhesion between the titania nanoparticles and the glass surface in Comparative Example 3 is lower than that in Example 1. When an antibacterial test against Escherichia coli (K-12) was performed using a method based on JISR1752 (brightness 600 lux, irradiation for 7 hours), the antibacterial activity value was 2.0. From Example 1 and Comparative Example 3, it can be understood that the visible light catalytic activity of Comparative Example 3 is inferior to that of Example 1. It can be understood that the antibacterial activity of the photocatalytic material increases when exposed to light, but the antibacterial effect is lower than that of Example 1, with a value of 2.0 even under light irradiation.
Claims
1. A metal-supported titania nanoparticle having a metal supported on the surface of the titania nanoparticle, The titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, When the titania nanoparticles are heated to 600°C using a thermogravimetric and differential thermal analyzer, the mass loss at 200°C or higher is 7 to 20% by mass; and The specific surface area of the titania nanoparticles is 200 to 400 m 2 / g; Both silver and copper are supported on the surface of the titania nanoparticles, The silver is in the form of silver nanoparticles having an average particle size of 10 to 200 nm, The form of the copper is at least one selected from the group consisting of copper nanoparticles and divalent copper ions, Metal-loaded titania nanoparticles.
2. 2. The metal-loaded titania nanoparticles according to claim 1, wherein the copper is in the form of divalent copper ions.
3. The metal-supported titania nanoparticles according to claim 1, wherein the copper is in the form of copper nanoparticles having an average particle size of 1 to 100 nm.
4. 2. The metal-supported titania nanoparticle according to claim 1, wherein the amount of the silver supported is 200 mass % or less based on the mass of titanium oxide in the titania nanoparticle.
5. 2. The metal-supporting titania nanoparticle according to claim 1, wherein the amount of the copper supported is 200 mass % or less based on the mass of titanium oxide in the titania nanoparticle.
6. The acyloxy group is bonded to a titanium atom via a group represented by -OCOR (wherein R represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a hydroxyalkyl group having 1 to 2 carbon atoms). The metal-supported titania nanoparticle according to any one of claims 1 to 5.
7. The acyloxy group is an acyloxy group derived from at least one organic acid selected from the group consisting of monocarboxylic acids having 1 to 4 carbon atoms and hydroxycarboxylic acids having 2 to 3 carbon atoms. The metal-supported titania nanoparticles according to any one of claims 1 to 5.
8. The metal-supported titania nanoparticles according to claim 7, wherein the organic acid is acetic acid and / or lactic acid.
9. A photocatalyst comprising the metal-supported titania nanoparticles according to any one of claims 1 to 8.
10. A method for producing the metal-supported titania nanoparticles according to any one of claims 1 to 8 or the photocatalyst according to claim 9, comprising the steps of: (A) mixing a titanium-containing substance, an organic acid, and water to obtain a dispersion; (B) subjecting the dispersion obtained in the step (A) to a temperature higher than 80° C. At atmospheric pressure for a period of at least 1 hour, or Under pressure for 5 to 30 minutes, A heating step; (C1) A step of irradiating ultraviolet light onto the dispersion obtained by mixing the dispersion obtained in the step (B), silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound; (C2) A step of mixing the dispersion obtained in the step (B), silver nanoparticles and / or a silver compound, and copper nanoparticles and / or a copper compound; or (C3) adding silver nanoparticles and / or a silver compound and copper nanoparticles and / or a copper compound to the dispersion liquid obtained in the step (B) and allowing the mixture to stand; Equipped with Manufacturing method.
11. 50% by mass or more of water; The metal-supported titania nanoparticles according to any one of claims 1 to 8 or the photocatalyst according to claim 9. A metal-supported titania nanoparticle dispersion comprising:
12. The metal-supported titania nanoparticle dispersion according to claim 11, which does not contain a dispersing agent.
13. A paint comprising the metal-supported titania nanoparticles according to any one of claims 1 to 8 or the photocatalyst according to claim 9.
14. A coating film comprising the metal-supported titania nanoparticles according to any one of claims 1 to 8, or the photocatalyst according to claim 9.
15. A coated product comprising the coating film according to claim 14.
Citation Information
Patent Citations
Titanium-containing material
JP2004507421A
Photocatalyst titanium oxide sol and coating composition using the same
JP2008260684A
Functional nanomaterials with antibacterial and antiviral activity
JP2009535326A
Virus inactivating agent
JP2013166705A
Precious metal-carrying titanium dioxide mesocrystal
JP2013236997A